Peran Pendidikan, Pelatihan, dan Pengalaman Mengajar dalam Meningkatkan Profesionalisme Guru SMA - Latifah Latifah; Mailatul Muyassaroh (OPTIMAL Jurnal Ekonomi dan Manajemen, 2021)
This study aims to explore the role of education, training and teaching experience in improving teacher professionalism in senior secondary schools. Teacher professionalism is key to achieving high and sustainable education quality, so it is important to understand the factors that can influence it. This study used a quantitative approach with a survey method, where data were collected through questionnaires distributed to 100 high school teachers in several schools in Jakarta. The results show that education, training, and teaching experience significantly contribute to improving teacher professionalism. Formal education obtained by teachers plays a role in expanding their knowledge and skills, while ongoing professional training provides opportunities to update and improve pedagogical skills. Extensive teaching experience, on the other hand, allows teachers to develop practical expertise and solve challenges faced in the classroom more effectively. The findings underscore the importance of integration between education, training and experience in efforts to improve teachers' professionalism, ultimately contributing to the quality of education at the senior secondary level.